West Nile Virus Transmission by Solid Organ Transplantation and Considerations for Organ Donor Screening Practices, United States - Soto, Raymond A.; McDonald, Emily; Annambhotla, Pallavi; Velez, Jason O.; Laven, Janeen; Panella, Amanda J.; Machesky, Kimberly D.; White, Jennifer L.; Hyun, Judie; Freuck, Emily; Habel, Janice; Oh, David; et al. (Emerging infectious diseases, 2022)
West Nile virus (WNV) is the most common domestic arbovirus in the United States. During 2018, WNV was transmitted through solid organ transplantation to 2 recipients who had neuroinvasive disease develop. Because of increased illness and death in transplant recipients, organ procurement organizations should consider screening during region-specific WNV transmission months.